A phosphorus removal adsorbent based on micro-nano air flotation coupled micro-flocculation and its preparation method

By combining the hydrophobic MOF polymer with polyacrylamide and modified hydroxyapatite to form a composite hydrogel, a phosphorus removal adsorbent based on micro-nano air-floating coupled microflocculation was prepared, which solved the problem of poor treatment of low-phosphorus wastewater and new pollutants in the prior art, and achieved deep treatment of phosphorus-containing wastewater and efficient adsorption of new pollutants.

CN119281308BActive Publication Date: 2025-03-18ANHUI HENGYU ENVIRONMENTAL PROTECTION EQUIPMENT MANUFACTURING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411828913.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art is not effective in treating new pollutants such as wastewater with low phosphorus content and microplastics, and the synergistic effect of micro-nano airflotation technology and flocculants is insufficient, resulting in a shallow degree of treatment of phosphorus-containing wastewater.

Method used

By uniformly combining the hydrophobic MOF polymer with polyacrylamide and modified hydroxyapatite to form a composite hydrogel, and a phosphorus removal adsorbent based on micro-nanogasflooding coupled microflocculation was prepared.

Benefits of technology

Under the synergistic action of the micro-nano gas-floating process, this phosphorus removal adsorbent significantly improves the adsorption capacity of phosphorus and new pollutants in wastewater, solves the problem of low binding force of micro-nano gas-floating on new pollutants and is prone to fall off, and realizes the in-depth treatment of phosphorus-containing wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a dephosphorization adsorbent based on micro-nano air flotation coupled micro-flocculation and a preparation method thereof. The method comprises the following steps: dissolving carboxymethyl chitosan, mixing the mixture with modified hydroxyapatite and a hydrophobic MOF polymer, polymerizing the mixture under the action of an initiator to obtain a composite hydrogel; curing the composite hydrogel in a calcium chloride solution, performing cyclic freezing-thawing and physical cross-linking to obtain a dephosphorization adsorbent; the invention combines an organic phosphorus adsorbent with an inorganic phosphorus adsorbent to enhance the adsorption capacity of the dephosphorization adsorbent on phosphorus, uniformly composites the hydrophobic MOF polymer having an adsorption effect on hydrophobic new pollutants with the organic phosphorus adsorbent, so that the dephosphorization adsorbent also has an adsorption effect on insoluble new pollutants in wastewater; under the synergistic effect of the micro-nano air flotation process, the new pollutants adsorbed by the micro-nano air flotation are adsorbed by the dephosphorization adsorbent, and the problem that the micro-nano air flotation has a low binding force on the new pollutants and is easy to fall off is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wastewater treatment, and in particular relates to a phosphorus removal adsorbent based on micro-nano air flotation coupled micro-flocculation and a preparation method thereof. Background Art

[0002] Eutrophication of water bodies can lead to outbreaks of blue-green algae, seriously damage the ecological environment of water bodies, reduce water functions, and cause mass deaths of aquatic organisms such as fish. Prominent problems such as eutrophication and new pollutants such as microplastics (EPS) have not yet been fundamentally solved. Blue-green algae blooms and water ecological imbalance problems still exist. The main pollution indicators are total phosphorus, chemical oxygen demand and permanganate index. Total phosphorus has become one of the three major pollution indicators of major surface water bodies and is an important issue that needs to be urgently addressed in the current water environment governance process.

[0003] Micro-nano bubble technology has been widely studied and applied in the field of water treatment due to its characteristics of long residence time, large specific surface area, enhanced mass transfer and no secondary pollution. At the same time, micro-nano bubbles carry a high negative charge and there is a double electric layer on the bubble surface. The repulsive force generated not only prevents the bubbles from combining with each other, but also has good adsorption for new pollutants in wastewater, which can enhance the synergistic removal of phosphorus and various pollutants in the water environment. However, micro-nano bubble technology has poor treatment effect on wastewater with low phosphorus content, and the adsorption force for new pollutants such as microplastics is small and easy to fall off, resulting in a shallow treatment degree of phosphorus-containing wastewater. Micro-nano bubble technology needs to be combined with flocculants to achieve deep treatment of phosphorus-containing wastewater.

[0004] Patent CN116535054A discloses a method for treating high-salt wastewater, which uses oxidants, ozone, micro-nano bubbles, and phosphorus removal agents, etc., and the mutual coordination between materials and process steps to achieve deep treatment of organic matter, organic phosphorus and total phosphorus; however, this solution uses ozone and oxidants to convert organic phosphorus into inorganic phosphorus, and then uses precipitants to flocculate and remove phosphorus. The resulting precipitated sludge is difficult to handle, easily causes secondary pollution, and has low synergy with the micro-nano flotation process. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to improve the synergistic effect of flocculants and micro-nano flotation on the treatment capacity of phosphorus and new pollutants in phosphorus-containing wastewater, and to provide a phosphorus removal adsorbent based on micro-nano flotation coupled with micro-flocculation and a preparation method thereof.

[0006] The present invention obtains a dephosphorization adsorbent capable of adsorbing phosphorus and new pollutants by uniformly combining a hydrophobic MOF polymer capable of adsorbing new pollutants with an organic phosphorus adsorbent made of polyacrylamide and an inorganic phosphorus adsorbent made of lanthanum-modified hydroxyapatite, and then forming the resulting spheres under the crosslinking action of carboxymethyl chitosan and calcium ions.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a phosphorus removal adsorbent based on micro-nano air flotation coupled with micro-flocculation comprises the following steps:

[0009] Step 1: Add carboxymethyl chitosan to deionized water in a reactor and heat and stir to dissolve, add modified hydroxyapatite and hydrophobic MOF polymer, ultrasonically disperse for 10-15 minutes, stir N-hexadecyl acrylamide and acrylamide in dimethyl sulfoxide until dissolved and add them to the reactor, then add potassium persulfate to the reactor, react at 50-55°C for 120-150 minutes under nitrogen protection to obtain a composite hydrogel.

[0010] Step 2: Use a syringe to drop the composite hydrogel into a calcium chloride solution with a concentration of 40-50 g / L, filter after the curing reaction for 2-3 hours, place the filtered hydrogel spheres in ethanol for 1-2 hours to remove water and unreacted monomers, filter again, wash the hydrogel spheres with deionized water, freeze at -20°C for 20 hours and thaw at room temperature for 4 hours, and obtain a phosphorus removal adsorbent after 3-5 cycles of freeze-thaw physical crosslinking.

[0011] Furthermore, in step 1, the dosage ratio of carboxymethyl chitosan, deionized water, modified hydroxyapatite, hydrophobic MOF polymer, N-hexadecyl acrylamide, acrylamide, dimethyl sulfoxide and potassium persulfate is 2-3 g: 50-60 mL: 0.3-0.5 g: 0.5-0.8 g: 3-5 g: 15-20 g: 40-50 mL: 0.03-0.05 g.

[0012] Further, the modified hydroxyapatite is prepared by the following steps:

[0013] The hydroxyapatite solution and the lanthanum chloride solution are mixed and stirred for 30-40 minutes, the pH value is adjusted to 10-11 with ammonia water, ultrasonic treatment is performed for 30-40 minutes, and then stirred for 3-4 hours. After standing for 12-14 hours, the supernatant is decanted, the precipitate is washed with deionized water and then filtered, and the obtained solid is dried at 70-80° C. for 8-10 hours, ground and sieved, and then placed in a muffle furnace for calcination at 300-350° C. for 5-6 hours to obtain modified hydroxyapatite.

[0014] Furthermore, the hydroxyapatite solution and the lanthanum chloride solution are obtained by dissolving hydroxyapatite and lanthanum chloride in deionized water at a ratio of 1 g:100 mL, respectively.

[0015] Furthermore, the usage ratio of hydroxyapatite and lanthanum chloride is 5-6g:0.5-0.6g.

[0016] Further, the hydrophobic MOF polymer is prepared by the following steps:

[0017] The hydrophobic polymer and 2-methylimidazole were ultrasonically dispersed in methanol in a reaction kettle, and a zinc nitrate methanol solution was added to the reaction kettle, followed by vigorous stirring for 20-24 hours. The precipitate was washed with methanol after centrifugation, and then vacuum dried at 55-65° C. for 10-12 hours and then crushed and sieved to obtain a hydrophobic MOF polymer.

[0018] The zinc nitrate methanol solution is prepared by mixing zinc nitrate hexahydrate and methanol in a dosage ratio of 1.5 g:100 mL.

[0019] Furthermore, the usage ratio of the hydrophobic polymer, 2-methylimidazole, methanol and zinc nitrate methanol solution is 8-12 g: 6-10 g: 200-300 mL: 200-300 mL.

[0020] Further, the hydrophobic polymer is prepared by the following steps:

[0021] In a reaction kettle, divinylbenzene and 1-vinylimidazole are added to a solution of azobisisobutyronitrile and ethyl acetate, and the mixture is stirred for 3-4 hours. The mixture is heated to 95-105° C. and reacted for 20-24 hours. The solvent is rotary evaporated and the solid precipitate is washed with ethyl acetate and methanol. The solid precipitate is vacuum dried at 70-80° C. to obtain a hydrophobic polymer.

[0022] Furthermore, the usage ratio of divinylbenzene, 1-vinylimidazole, azobisisobutyronitrile and ethyl acetate is 4-5 g: 1-1.2 g: 0.15-0.2 g: 30-40 mL.

[0023] The dephosphorus adsorbent prepared by the present invention combines an organic phosphorus adsorbent and an inorganic phosphorus adsorbent to enhance the adsorption capacity of the dephosphorus adsorbent on phosphorus in wastewater, and uniformly compounds a hydrophobic MOF polymer that has an adsorption effect on hydrophobic new pollutants with the organic phosphorus adsorbent, so that the dephosphorus adsorbent has an efficient adsorption effect on phosphorus and also has an adsorption effect on insoluble new pollutants in wastewater. Under the synergistic effect of the micro-nano flotation process, the new pollutants adsorbed by the micro-nano flotation are adsorbed by the dephosphorus adsorbent, thereby solving the problem that the micro-nano flotation has a low binding force on the new pollutants and is easy to fall off.

[0024] The preparation method of the invention adds hydrophobic N-hexadecyl acrylamide during the polymerization of acrylamide, so that the synthesized polyacrylamide has a partial hydrophobic segment, and the hydrophobic MOF polymer can be combined with the polyacrylamide by utilizing the hydrophobic segment of the polyacrylamide, and the hydroxyl groups on the surface of the modified hydroxyapatite are covalently combined with carboxymethyl chitosan, and the modified hydroxyapatite is uniformly combined with the polyacrylamide by utilizing the double network structure formed by cross-linking carboxymethyl chitosan and polyacrylamide, and the modified hydroxyapatite and the hydrophobic MOF polymer in the formed composite hydrogel have good dispersibility and produce synergistic effect with the polyacrylamide, so that the obtained phosphorus removal adsorbent has a strong adsorption effect on phosphorus. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1: A method for preparing a phosphorus removal adsorbent based on micro-nano air flotation coupled with micro-flocculation, comprising the following steps:

[0027] Step 1: Add 4 g of divinylbenzene and 1 g of 1-vinylimidazole to a solution of 0.15 g of azobisisobutyronitrile and 30 mL of ethyl acetate in a reaction kettle, stir and mix for 3 h, heat to 95 ° C and react for 20 h, rotary evaporate the solvent and wash the solid precipitate with ethyl acetate and methanol, and vacuum dry at 70 ° C to obtain a hydrophobic polymer.

[0028] Step 2: In a reactor, 8 g of a hydrophobic polymer and 6 g of 2-methylimidazole are ultrasonically dispersed in 200 mL of methanol, and 200 mL of zinc nitrate methanol solution is added to the reactor. The zinc nitrate methanol solution is prepared by mixing zinc nitrate hexahydrate and methanol in a dosage ratio of 1.5 g: 100 mL. The mixture is then stirred vigorously for 20 h. After centrifugation, the precipitate is washed with methanol, and then crushed and sieved to obtain a hydrophobic MOF polymer after vacuum drying at 55 °C for 10 h.

[0029] Step 3: In a reaction kettle, 5 g of hydroxyapatite and 0.5 g of lanthanum chloride were dissolved in deionized water at a ratio of 1 g: 100 mL to obtain a hydroxyapatite solution and a lanthanum chloride solution, hydrochloric acid was added dropwise to the lanthanum chloride solution until the solution became transparent, and then the hydroxyapatite solution and the lanthanum chloride solution were mixed and stirred for 30 minutes, the pH value was adjusted to 10 with ammonia water, ultrasonically treated for 30 minutes, stirred for 3 hours, and allowed to stand for 12 hours, and the supernatant was decanted. The precipitate was washed with deionized water and filtered, and the obtained solid was dried at 70°C for 8 hours, ground and sieved, and then calcined in a muffle furnace at 300°C for 5 hours to obtain modified hydroxyapatite.

[0030] Step 4: Add 2 g of carboxymethyl chitosan to 50 mL of deionized water in a reactor and heat and stir to dissolve, add 0.3 g of modified hydroxyapatite and 0.5 g of hydrophobic MOF polymer, and ultrasonically disperse for 10 min. Stir 3 g of N-hexadecyl acrylamide and 15 g of acrylamide in 40 mL of dimethyl sulfoxide until dissolved and add them to the reactor. Then add 0.03 g of potassium persulfate to the reactor to initiate the polymerization reaction. React at 50 ° C for 120 min under nitrogen protection to obtain a composite hydrogel.

[0031] Step 5. Use a syringe to drop the composite hydrogel into a calcium chloride solution with a concentration of 40 g / L, filter after the curing reaction for 2 hours, place the filtered hydrogel spheres in ethanol for 1 hour to remove water and unreacted monomers, filter again, wash the hydrogel spheres with deionized water, freeze at -20°C for 20 hours and thaw at room temperature for 4 hours, and obtain a phosphorus removal adsorbent after 3 cycles of freeze-thaw physical crosslinking.

[0032] Example 2: A method for preparing a phosphorus removal adsorbent based on micro-nano flotation coupled micro-flocculation, comprising the following steps:

[0033] Step 1: Add 4.5 g of divinylbenzene and 1.1 g of 1-vinylimidazole to a solution of 0.17 g of azobisisobutyronitrile and 35 mL of ethyl acetate in a reaction kettle, stir and mix for 3.5 h, heat to 100 ° C and react for 22 h, rotary evaporate the solvent, wash the solid precipitate with ethyl acetate and methanol, and vacuum dry at 75 ° C to obtain a hydrophobic polymer.

[0034] Beneficial effects of the present invention:

[0035] Step 2: Ultrasonically disperse 10 g of a hydrophobic polymer and 8 g of 2-methylimidazole in 250 mL of methanol in a reactor, add 250 mL of zinc nitrate methanol solution into the reactor, the zinc nitrate methanol solution is prepared by mixing zinc nitrate hexahydrate and methanol in a dosage ratio of 1.5 g: 100 mL, then vigorously stir and react for 22 hours, wash the precipitate with methanol after centrifugation, and vacuum dry it at 60°C for 11 hours, then crush and sieve to obtain a hydrophobic MOF polymer.

[0036] Step 3. In a reaction kettle, 5.5 g of hydroxyapatite and 0.55 g of lanthanum chloride were respectively dissolved in deionized water at a ratio of 1 g: 100 mL to obtain a hydroxyapatite solution and a lanthanum chloride solution. Hydrochloric acid was added dropwise to the lanthanum chloride solution until the solution became transparent. The hydroxyapatite solution and the lanthanum chloride solution were mixed and stirred for 35 minutes. The pH value was adjusted to 10.5 with ammonia water, and ultrasonic treatment was performed for 35 minutes and then stirred for 3.5 hours. After standing for 13 hours, the supernatant was decanted, the precipitate was washed with deionized water and filtered, and the obtained solid was dried at 75° C. for 9 hours. After grinding and sieving, it was placed in a muffle furnace at 325° C. and calcined for 5.5 hours to obtain modified hydroxyapatite.

[0037] Step 4: Add 2.5 g of carboxymethyl chitosan to 55 mL of deionized water in a reactor and heat and stir to dissolve, add 0.4 g of modified hydroxyapatite and 0.65 g of hydrophobic MOF polymer, and ultrasonically disperse for 12.5 min. Stir 4 g of N-hexadecyl acrylamide and 17.5 g of acrylamide in 45 mL of dimethyl sulfoxide until dissolved and add them to the reactor. Then add 0.04 g of potassium persulfate to the reactor to initiate the polymerization reaction. React at 52.5 ° C for 135 min under nitrogen protection to obtain a composite hydrogel.

[0038] Step 5. Use a syringe to drop the composite hydrogel into a calcium chloride solution with a concentration of 45 g / L, filter after the curing reaction for 2.5 hours, place the filtered hydrogel spheres in ethanol for 1.5 hours to remove water and unreacted monomers, filter again, wash the hydrogel spheres with deionized water, freeze at -20°C for 20 hours and thaw at room temperature for 4 hours, and obtain a phosphorus removal adsorbent after 4 cycles of freeze-thaw physical crosslinking.

[0039] Example 3: A method for preparing a phosphorus removal adsorbent based on micro-nano flotation coupled micro-flocculation, comprising the following steps:

[0040] Step 1: Add 5 g of divinylbenzene and 1.2 g of 1-vinylimidazole to a solution of 0.2 g of azobisisobutyronitrile and 40 mL of ethyl acetate in a reaction kettle, stir and mix for 4 h, heat to 105 ° C and react for 24 h, rotary evaporate the solvent and wash the solid precipitate with ethyl acetate and methanol, and vacuum dry at 80 ° C to obtain a hydrophobic polymer.

[0041] Step 2: Ultrasonically disperse 12 g of a hydrophobic polymer and 10 g of 2-methylimidazole in 300 mL of methanol in a reactor, add 300 mL of zinc nitrate methanol solution into the reactor, the zinc nitrate methanol solution is prepared by mixing zinc nitrate hexahydrate and methanol in a dosage ratio of 1.5 g: 100 mL, then vigorously stir and react for 24 hours, wash the precipitate with methanol after centrifugation, and vacuum dry it at 65°C for 12 hours, then crush and sieve to obtain a hydrophobic MOF polymer.

[0042] A super-hydrophobic porous hydrophobic polymer is generated by polymerizing divinylbenzene and 1-vinylimidazole under the action of an initiator, and a microporous MOF material is in situ grown in the pores of the hydrophobic polymer. The obtained hydrophobic MOF polymer has excellent hydrophobic properties, so that solid particles such as new pollutants (Eps) in wastewater are adsorbed by the hydrophobic MOF polymer under the hydrophobic force and the adsorption of porous materials.

[0043] Step 3: In a reaction kettle, 6 g of hydroxyapatite and 0.6 g of lanthanum chloride were respectively dissolved in deionized water at a ratio of 1 g: 100 mL to obtain a hydroxyapatite solution and a lanthanum chloride solution. Hydrochloric acid was added dropwise to the lanthanum chloride solution until the solution became transparent. The hydroxyapatite solution and the lanthanum chloride solution were mixed and stirred for 40 minutes. The pH value was adjusted to 11 with ammonia water, and ultrasonic treatment was performed for 40 minutes and then stirred for 4 hours. After standing for 14 hours, the supernatant was decanted, the precipitate was washed with deionized water and filtered, and the obtained solid was dried at 80° C. for 10 hours, ground and sieved, and then calcined in a muffle furnace at 350° C. for 6 hours to obtain modified hydroxyapatite.

[0044] The rare earth metal lanthanum has high affinity for phosphorus, high adsorption capacity, fast adsorption efficiency and selectivity. By modifying hydroxyapatite with rare earth elements, the adsorption of hydroxyapatite on phosphorus is improved.

[0045] Step 4: Add 3 g of carboxymethyl chitosan to 60 mL of deionized water in a reactor and heat and stir to dissolve, add 0.5 g of modified hydroxyapatite and 0.8 g of hydrophobic MOF polymer, and ultrasonically disperse for 15 min. Stir 5 g of N-hexadecyl acrylamide and 20 g of acrylamide in 50 mL of dimethyl sulfoxide until dissolved and add them to the reactor. Then add 0.05 g of potassium persulfate to the reactor to initiate the polymerization reaction. React at 55 ° C for 150 min under nitrogen protection to obtain a composite hydrogel.

[0046] The modified hydroxyapatite is combined in the polymer chain by utilizing the hydrogen bonding effect formed by the polymer chain formed by acrylamide and carboxymethyl chitosan and the hydroxyl groups on the surface of the modified hydroxyapatite, and the inorganic phosphorus adsorbent and the organic phosphorus adsorbent are evenly compounded to improve the adsorption effect of phosphorus in the wastewater; the hydrophobic MOF polymer is grafted onto the hydrophobic segment in the polymer chain by utilizing the hydrophobic force, so that the polymer chain has the adsorption effect on new hydrophobic pollutants, thereby improving the adsorption capacity of the adsorbent for new pollutants in the wastewater.

[0047] Step 5. Use a syringe to drop the composite hydrogel into a calcium chloride solution with a concentration of 50 g / L, filter after the curing reaction for 3 hours, place the filtered hydrogel spheres in ethanol for 2 hours to remove water and unreacted monomers, filter again, wash the hydrogel spheres with deionized water, freeze at -20°C for 20 hours and thaw at room temperature for 4 hours, and obtain a phosphorus removal adsorbent after 5 cycles of freeze-thaw physical crosslinking.

[0048] The composite hydrogel is solidified by cross-linking the carboxymethyl chitosan in the composite hydrogel with calcium ions. The obtained phosphorus removal adsorbent contains partially hydrophobically modified polyacrylamide as an organic phosphorus adsorbent and lanthanum-modified hydroxyapatite as an inorganic phosphorus adsorbent. The organic phosphorus adsorbent and the inorganic phosphorus adsorbent are evenly compounded, which improves the adsorption effect of the phosphorus removal adsorbent on phosphorus. At the same time, the high swelling ratio of carboxymethyl chitosan increases the contact area of ​​the phosphorus removal adsorbent with phosphorus and new pollutants in the water body, further improving the adsorption effect of the phosphorus removal adsorbent; the partially hydrophobically modified polyacrylamide combines the hydrophobic MOF polymer by hydrophobic binding and hydrogen bonding, so that the hydrophobic MOF polymer is evenly combined in the composite hydrogel. The hydrophobic MOF polymer adsorbs insoluble new pollutants in the wastewater under the hydrophobic force and the adsorption force of the hydrophobic MOF polymer, which improves the adsorption effect of the phosphorus removal adsorbent on the new pollutants. Under the coupling effect of micro-nano flotation, the new pollutants are discharged along with the phosphorus removal adsorbent, so as to achieve the effect of purifying the wastewater.

[0049] Comparative Example 1: The difference from Example 1 is that a hydrophobic polymer is used instead of a hydrophobic MOF polymer to prepare a phosphorus removal adsorbent.

[0050] Comparative Example 2: The difference from Example 1 is that in step 4, no modified hydroxyapatite is added to obtain a composite hydrogel, and a phosphorus removal adsorbent is prepared using the composite hydrogel.

[0051] Comparative Example 3: The difference from Example 1 is that in step 4, N-hexadecyl acrylamide is not added to obtain a composite hydrogel, and a phosphorus removal adsorbent is prepared using the composite hydrogel.

[0052] The performance of the phosphorus removal adsorbents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested. The simulated phosphorus-containing wastewater with a concentration of 200 mg / L was prepared with potassium dihydrogen phosphate, and 2.5 g of the phosphorus removal adsorbent was added to 500 mL of the simulated phosphorus-containing wastewater. Air was introduced into the simulated phosphorus-containing wastewater using a micro-nano bubble generator, and the dissolved gas pressure was 0.25 MPa. The treatment time was 30 min. After separating the phosphorus removal adsorbent, the phosphorus concentration of the filtrate was measured using a 0.22 μm inorganic filter membrane, and the phosphorus removal rate was calculated; a 1 g / L microplastic suspension was prepared using 10 μm PP microplastics, 2.5 g of the phosphorus removal adsorbent was added to 500 mL of the microplastic suspension, and air was introduced into the microplastic suspension using a micro-nano bubble generator. The dissolved gas pressure was 0.25 MPa, and the treatment time was 30 min. After separating the phosphorus removal adsorbent, the change in the concentration of PP microplastics before and after adsorption of the suspension was measured by fluorescence detection, and the adsorption rate was calculated. The results are shown in Table 1:

[0053] Table 1 Phosphorus removal rate and microplastic adsorption rate of phosphorus removal adsorbent

[0054]

[0055] It can be seen from Table 1 that the phosphorus removal adsorbent prepared by the present invention has a high removal rate of phosphorus in wastewater under the synergy of the micro-nano flotation process. After 30 minutes of treatment, the phosphorus removal rate reaches more than 94%, and the removal rate of phosphorus is high. The phosphorus removal adsorbent prepared by the present invention has a high adsorption rate for microplastics, indicating that the phosphorus removal adsorbent prepared by the present invention has a good adsorption effect on hydrophobic microplastics, and can remove new pollutants such as insoluble matter in wastewater while removing phosphorus, and has high wastewater purification efficiency; Comparative Example 1 does not generate MOF material in situ in the pores of the hydrophobic polymer , the adsorption effect of the hydrophobic polymer is low, and the adsorption effect on microplastics is weak; in Comparative Example 2, since modified hydroxyapatite is not added, the phosphorus removal adsorbent obtained has only polyacrylamide adsorption effect, and the single polyacrylamide has limited adsorption effect on phosphorus, so the phosphorus removal rate is low; in Comparative Example 3, since hydrophobic segments are not added during the polymerization of polyacrylamide to partially hydrophobically modify the polyacrylamide, the hydrogen bonding effect of the hydrophobic polymer in the composite hydrogel is weak and the dispersion is uneven, the adsorption capacity of the obtained phosphorus removal adsorbent is weakened, and the adsorption effect on microplastics is also reduced.

[0056] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0057] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a phosphorus removal adsorbent based on micro-nano flotation coupled micro-flocculation, characterized in that: The steps include: Step 1, in a reactor, add carboxymethyl chitosan into deionized water and heat and stir to dissolve, add modified hydroxyapatite and hydrophobic MOF polymer, ultrasonically disperse for 10-15 minutes, stir N-hexadecyl acrylamide and acrylamide in dimethyl sulfoxide until dissolved and add them into the reactor, then add potassium persulfate into the reactor, react at 50-55° C. for 120-150 minutes under nitrogen protection, and obtain a composite hydrogel; Step 2: Use a syringe to drop the composite hydrogel into a calcium chloride solution with a concentration of 40-50 g / L, filter after curing reaction for 2-3 hours, place the filtered hydrogel spheres in ethanol for 1-2 hours to remove water and unreacted monomers, filter again and wash the hydrogel spheres with deionized water, freeze at -20°C for 20 hours and thaw at room temperature for 4 hours, and obtain a phosphorus removal adsorbent after 3-5 cycles of freeze-thaw physical crosslinking; The amount ratio of carboxymethyl chitosan, deionized water, modified hydroxyapatite, hydrophobic MOF polymer, N-hexadecyl acrylamide, acrylamide, dimethyl sulfoxide and potassium persulfate in step 1 is 2-3g: 50-60mL: 0.3-0.5g: 0.5-0.8g: 3-5g: 15-20g: 40-50mL: 0.03-0.05g; The modified hydroxyapatite is prepared by the following steps: The hydroxyapatite solution and the lanthanum chloride solution are mixed and stirred for 30-40 minutes, the pH value is adjusted to 10-11 with ammonia water, ultrasonically treated for 30-40 minutes, stirred for 3-4 hours, allowed to stand for 12-14 hours, the supernatant is decanted, the precipitate is washed with deionized water and filtered, the obtained solid is dried at 70-80° C. for 8-10 hours, ground and sieved, and then calcined in a muffle furnace at 300-350° C. for 5-6 hours to obtain modified hydroxyapatite; The hydrophobic MOF polymer is prepared by the following steps: In a reaction kettle, a hydrophobic polymer and 2-methylimidazole are ultrasonically dispersed in methanol, a zinc nitrate methanol solution is added to the reaction kettle, and then the reaction is vigorously stirred for 20-24 hours, and the precipitate is washed with methanol after centrifugation, and then vacuum dried at 55-65° C. for 10-12 hours, and then crushed and sieved to obtain a hydrophobic MOF polymer; The usage ratio of the hydrophobic polymer, 2-methylimidazole, methanol and zinc nitrate methanol solution is 8-12 g: 6-10 g: 200-300 mL: 200-300 mL; The zinc nitrate methanol solution is prepared by mixing zinc nitrate hexahydrate and methanol in a dosage ratio of 1.5 g:100 mL.

2. The method for preparing a phosphorus removal adsorbent based on micro-nano air flotation coupled micro-flocculation according to claim 1, characterized in that: The hydroxyapatite solution and the lanthanum chloride solution are obtained by dissolving hydroxyapatite and lanthanum chloride in deionized water at a ratio of 1 g:100 mL, respectively.

3. The method for preparing a phosphorus removal adsorbent based on micro-nano air flotation coupled micro-flocculation according to claim 2, characterized in that: The mass ratio of the hydroxyapatite to lanthanum chloride is 5-6:0.5-0.

6.

4. The method for preparing a phosphorus removal adsorbent based on micro-nano air flotation coupled micro-flocculation according to claim 1, characterized in that: The hydrophobic polymer is prepared by the following steps: In a reaction kettle, divinylbenzene and 1-vinylimidazole are added to a solution of azobisisobutyronitrile and ethyl acetate, and the mixture is stirred for 3-4 hours. The mixture is heated to 95-105° C. and reacted for 20-24 hours. The solvent is rotary evaporated and the solid precipitate is washed with ethyl acetate and methanol. The solid precipitate is vacuum dried at 70-80° C. to obtain a hydrophobic polymer.

5. The method for preparing a phosphorus removal adsorbent based on micro-nano air flotation coupled micro-flocculation according to claim 4, characterized in that: The usage ratio of divinylbenzene, 1-vinylimidazole, azobisisobutyronitrile and ethyl acetate is 4-5g:1-1.2g:0.15-0.2g:30-40mL.

6. A phosphorus removal adsorbent based on micro-nano flotation coupled micro-flocculation, characterized in that: The dephosphorus adsorbent is prepared by the preparation method of a micro-nano flotation coupled micro-flocculation adsorbent as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Amphoteric polymeric flocculant for removing phosphor in sewage

    CN101560005A

  • Porous nano fiber capable of rapidly adsorbing heavy metal ions and preparation method thereof

    CN106179238A